Predictive Value of Uric Acid Regarding Cardiometabolic Disease in a Community-Dwelling Older Population in Shanghai: A Cohort Study - Lan, Qin; Wu, Hong; Zhou, Xiaohui; Zheng, Liang; Lin, Fang; Meng, Qingshu; Xi, Xiaoling; Yue, Aixue; Buys, Nicholas; Sun, Jing; Liu, Zhongmin; Li, Jue; et al. (Frontiers in Medicine, 2020)
Aim: This study aimed to test the predictive power of serum uric acid (UA) levels on new-onset cardiometabolic risk in the Chinese population. Methods: Older people who visited a community health center for a yearly health check (N = 5,000; men: 47%, women: 53%) were enrolled. Participants were followed for four years from baseline (median: 48 months), with the endpoints being development of heart failure, atrial fibrillation, diabetes, hypertension, metabolic syndrome, or kidney disease. Results: During follow-up, 342 men (7.4%) and 360 women (8.6%) developed hypertension; 98 men (2.48%) and 135 women (3.06%) developed diabetes; and 175 men (5.04%) and 214 women (4.51%) developed metabolic syndrome. Incident diabetes, hypertension, and metabolic syndrome increased with increased UA levels at baseline (P < 0.001). A multivariate Cox proportional hazards analysis revealed a significant, independent association between the baseline UA level and the onset and future hypertension and/or diabetes in both men and women. However, UA is associated with the development of metabolic syndrome in men, but not in women. Conclusion: UA is an independent predictor of new-onset diabetes and hypertension in both women and men and a predictor of new-onset metabolic syndrome only in men.